2018
DOI: 10.1017/jfm.2018.939
|View full text |Cite
|
Sign up to set email alerts
|

The onset of dynamic stall at a high, transitional Reynolds number

Abstract: Dynamic stall due to a ramp-type pitching motion is investigated on the NACA 0012 airfoil at chord Reynolds number of $Re_{c}=1.0\times 10^{6}$ through the use of wall-resolved large-eddy simulation. Emphasis is placed on the unsteady boundary-layer interactions that develop as the airfoil approaches stall. At this Reynolds number it is shown that turbulent separation moves upstream across much of the airfoil suction surface. When turbulent separation reaches the leading-edge separation bubble, a bursting even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(45 citation statements)
references
References 45 publications
3
42
0
Order By: Relevance
“…This transient pressure feature has also been observed in the simulations of Benton and Visbal. [21,22] Finally, the overall fluctuation energy at moderate and high frequencies is observed, from Fig. 3.18 a), to diminish rapidly for angles of attack beyond the suction peak.…”
Section: Pressure Evolution and Spectramentioning
confidence: 85%
See 3 more Smart Citations
“…This transient pressure feature has also been observed in the simulations of Benton and Visbal. [21,22] Finally, the overall fluctuation energy at moderate and high frequencies is observed, from Fig. 3.18 a), to diminish rapidly for angles of attack beyond the suction peak.…”
Section: Pressure Evolution and Spectramentioning
confidence: 85%
“…Gross [20], who also used LES to study the flow behavior about a Sirkosky SCC-A09 airfoil at Re c = 0.2×10 6 , for complex motion profiles, which included non-inertial effects from the centrifugal and Coriolis forces. The criticality of the LSB to dynamic stall onset was investigated even further in the recent numerical simulations of Benton and Visbal [21,22] involving an NACA 0012 geometry subjected to a constant-pitch rate maneuver at Re c = 1.0 × 10 6 . These authors demonstrated that, for the given flow conditions, the LSB breakdown was initiated by a direct interaction with the turbulent separation that starts from the airfoil trailing edge and propagates upstream with increasing angles of attack.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The loads on a VAWT can successfully be reproduced with numerical methods like large-or detached-eddy simulations, but underlying flow dynamics such as the onset of leading-edge vortices or the occurrence of the vortex shedding are not always reproducible with satisfying accuracy (Ferreira et al 2007). In parallel, experimental research is carried out on dynamic stall and its influence on VAWT, such as in Buchner et al (2017) or Miller et al (2018), or with a focus on simplified models like pitching plates or profiles (Benton and Visbal 2019) in order to provide deeper insights in the underlying mechanism and to develop control strategies for technical applications.…”
Section: Introductionmentioning
confidence: 99%